PENGARUH PENDEKATAN PROBLEM-BASED LEARNING BERMUATAN BUDAYA LOKAL KABUPATEN SUMEDANG TERHADAP KEMAMPUAN PEMAHAMAN DAN PEMECAHAN MATEMATIS - Pitriani, Desi; Irawati, Riana; 'atun, Isrok (Jurnal Pena Ilmiah, 2019)
The purpose of this study was to determine the increase in the ability to understand and solve mathemadarical problems using the Problem Based Learning approach in fracdarion material. This study used a quasi-experimental method and design research design for nonquivalent control groups. The study populadarion was all class II Cisarua sub-districts with samples of class II experimental class students at SDN Cisalak II and class II students at SDN Cisalak III in the control class. The conclusions of this study: 1) Problem Based Learning with the content of the local culture of Sumedang Regency to improve understanding skills, 2) Problem Based Learning with the contents of the local culture of Sumedang Regency to improve mathemadarical problem solving abilidaries 3) Problem Based Learning with the local culture of Sumedang Regency improve understanding and problem solving skills mathemadarically compared to convendarional learning.